2020
DOI: 10.14786/flr.v8i1.473
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Macro-Level Navigation Patterns in Hypermedia and their Relation with Task Structure and Learning Outcomes

Abstract: This study investigated macro-level navigation patterns in children's hypermedia learning, and how they related to task structure and learning outcomes. For this purpose, 5th and 6th grade learners performed a hypermedia assignment in which a high (n=57) versus a low (n=54) level of structure was provided. By means of qualitative analyses of their navigation activities, 6 macro-level navigation patterns were distinguished: linear reading, selective reading, video viewing, massed writing, late onset writing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…We, therefore, considered their reading behaviour as strategic. Nevertheless, future research could incorporate (retrospective) think-aloud interviews (Paans et al, 2020 ) based on students’ eye-moves through the text. This could provide information on the level of consciousness of possible reading choices.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, considered their reading behaviour as strategic. Nevertheless, future research could incorporate (retrospective) think-aloud interviews (Paans et al, 2020 ) based on students’ eye-moves through the text. This could provide information on the level of consciousness of possible reading choices.…”
Section: Discussionmentioning
confidence: 99%
“…A recent hypermedia study confirmed this line of thought and found that learners more often used a linear reading pattern in higher structured learning environments with more external regulation (Paans et al, 2020 ). Another study showed that learners’ approach of a task can be affected by task conditions (Pieschl et al, 2012 ).…”
Section: Navigation In Multimedia Learning Environmentsmentioning
confidence: 77%
“…An example of a study using such log data to examine learners’ navigation activities in a (hyper)media setting used plotted graphs in which was shown when learners moved to a different page in the multimedia environment. Paans et al ( 2020 ) showed that various navigation patterns could be distinguished, e.g., linear reading, selective reading, and unpredictable reading. These navigation patterns differed in terms of linearity with which students went through the online learning material.…”
Section: Visualizing Self-regulation In Multimedia Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to gain insight into groups' depth and social sharedness of metacognitive regulation during TOR is by looking at the learning process (Malmberg et al, 2013;Paans et al, 2020). For this reason, we executed an exploratory qualitative analysis to visualize the depth and sharedness across the four lessons.…”
Section: Methodsmentioning
confidence: 99%